THE NATIONAL UP-BRINGING OF CHILDREN AND YOUNG PEOPLE AS A PRIORITY DIRECTION OF THE WORK OF PUBLIC SOCIETIES IN VOLYN REGION IN THE 20-30 YEARS OF THE XX CENTURY - Marchuk, O.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The author of the article examines the national upbringing of children and youth which was carried out by the activists of the public organizations of Volyn province in the 20-30 years of the twentieth century. The purpose of the article is to explore the basic methods, forms and techniques of the national upbringing of the young generation in public societies. The author has used theoretical (scientific-bibliographic, historical-logical, historical-retrospective) and empirical (analysis, synthesis, comparison, generalization) methods to get the results. It is substantiated that the work of the members of public associations was contributed to the formation of patriotism and national ideals in the young generation. The article describes the meaning of the term national education. The largest organization were the «Union of Ukrainian women», «Prosvita», «Sokil», and «Rivne Boyan». The members of these societies held lectures, literary holidays, concerts, Christmas tree festivities. They cooperated with educational institutions. The teachers also participated in the national-patriotic holidays. Every year they held memorial meetings of T. Shevchenko, Lesia Ukrainka and I. Franko. Pupils, students and young people were reading poems, singing folk songs and staged performances. The members of the societies urged children and young people to study the elements of the folk costume and to preserve the folk crafts. The purpose of educational work of the activists of Volyn was to promote the national ideals. The pedagogical experience of the members of the Volyn societies should be used in modern schools. Today it is advisable to use the pedagogical and educational experience of activists of public associations of Volyn in the following directions: a) developing of the education system using the patriotic values; b) the involvement in the educational process of the national heroes, volunteers, persons who has got an active life position and promote the advocacy of the state interests; c) updating the forms and the methods of national education using the rapid development of computer technologies, in the introduction of the technologies of Smart education.